2013
DOI: 10.1038/bjc.2013.594
|View full text |Cite
|
Sign up to set email alerts
|

Phase II study of dovitinib in patients with metastatic and/or unresectable gastrointestinal stromal tumours after failure of imatinib and sunitinib

Abstract: Background:This prospective, phase II trial evaluated the efficacy and safety of dovitinib in patients with metastatic and/or unresectable gastrointestinal stromal tumours (GISTs) after failure of at least imatinib and sunitinib.Methods:Patients received oral dovitinib, 500 mg once daily, for 5 consecutive days, followed by a 2-day rest, every 28 days. The primary endpoint was disease control rate (DCR; objective response+stable disease (SD)) at 24 weeks, assessed by computed tomography (CT) scan according to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
30
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(34 citation statements)
references
References 36 publications
4
30
0
Order By: Relevance
“…Hypertension was observed in six (14%) patients. Overall, the dovitinib safety profile was consistent with previous reports on other indications and with other anti-VEGFR targeted therapies [14,21]. Although the most common treatment-associated AEs in this study occurred less frequently than previously reported for patients with metastatic renal cell carcinoma (RCC), [21] this finding may reflect the shorter median duration of exposure (7.5 weeks in this study versus 14.3 weeks in the RCC study).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Hypertension was observed in six (14%) patients. Overall, the dovitinib safety profile was consistent with previous reports on other indications and with other anti-VEGFR targeted therapies [14,21]. Although the most common treatment-associated AEs in this study occurred less frequently than previously reported for patients with metastatic renal cell carcinoma (RCC), [21] this finding may reflect the shorter median duration of exposure (7.5 weeks in this study versus 14.3 weeks in the RCC study).…”
Section: Discussionsupporting
confidence: 89%
“…Serum dovitinib concentrations after the 500-mg dose (14-453 ng/mL) were in the expected range [13,14]. Nearly all statistically significant mean fold-changes from baseline in serum biomarker levels with treatment occurred in the FGFR3 WT group, including increases in PlGF and VEGF and decreases in sVEGFR2 and CKIT (Table A.1; Fig.…”
Section: Pharmacokinetics and Biomarker Dynamicsmentioning
confidence: 88%
“…QTc prolongation was common (37%) in patients with hepatic impairment treated with bosutinib,10 but this was not seen in other smaller studies 11, 12. QTc prolongation was infrequent or absent with afatinib, crizotinib, ceritinib, dovitinib, imatinib, lapatinib, lenvatinib, nintedanib, pazopanib, and ponatinib 9, 14, 16, 17, 19, 24, 26, 27, 29, 30, 31, 32, 33, 35, 36, 38, 39, 72, 78, 81, 161, 162, 163, 164…”
Section: Resultsmentioning
confidence: 96%
“…Studies have shown that aspirin may suppress cancer cell growth by blocking the PI3K pathway and inducing apoptosis (Uddin et al, 2010). Furthermore, regular aspirin use after diagnosis of colorectal cancer was associated with longer survival in those patients with mutated PIK3CA colorectal cancer (Kang et al, 2013).…”
Section: Pi3kmentioning
confidence: 99%